A Novel Technique of Repositioning Papilla to Create a Balanced Anterior Pink and White Esthetics - Shrestha, Prabhta; Shakya, S. (Journal of Nepalese Prosthodontic Society, 2018)
The ultimate goal in modern era dentistry is to achieve the balance of “white” and “pink” in esthetically important zones. “White esthetics” is the natural dentition or the restoration of dental hard tissues with suitable materials. “Pink esthetics” refers to the surrounding soft-tissues, which includes the interdental papilla and gingiva that can enhance or diminish the esthetic result. This paper aims to describe a careful diagnosis and multidisciplinary treatment approach to achieve a satisfactory final esthetic outcome in a clinical scenario where there is an abnormal shape, position of tooth and displaced papilla in the anterior esthetic zone.